2014
DOI: 10.1142/s0219633614500370
|View full text |Cite
|
Sign up to set email alerts
|

Study on the cooperativity of hydrogen bonds betweenH2YandHX(X=F,Cl,Br;Y=O,S,Se)

Abstract: The structure characteristics, interaction energies, cooperative energies of the complexes between chalcogen hydrides ( H 2 Y ) and halogen hydrides (HX) have been studied theoretically at the MP2 level with aug-cc-pVTZ basis set in this paper. The conclusions show that there are strong interactions between H 2 Y and HX. The stability of the complex is decided by the electronegativity of the negatively charged atom. The cooperativity is observed in the two or three hydrogen bonds of each trimer structures in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…Liu et al reported a similar trend that the HX•••nH2O was more stable than HX•••nH2S, with X = F, Cl, Br. [33] The result shows that the larger the electronegativity of the atoms is, the stronger the stability of the corresponding complex is. In this study, the much larger electronegativity of O in H2O as compared to S in H2S is the reason why the R-nO complexes are much more stable than R-nS ones.…”
Section: Interaction Energies and Cooperativitymentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al reported a similar trend that the HX•••nH2O was more stable than HX•••nH2S, with X = F, Cl, Br. [33] The result shows that the larger the electronegativity of the atoms is, the stronger the stability of the corresponding complex is. In this study, the much larger electronegativity of O in H2O as compared to S in H2S is the reason why the R-nO complexes are much more stable than R-nS ones.…”
Section: Interaction Energies and Cooperativitymentioning
confidence: 99%
“…Liu et al reached a similar conclusion on cooperative ability of HX•••2H2Z (X = F, Cl, Br; Z = O, S), in which the HX•••2H2O cooperative energy is much more negative than the HX•••2H2S ones. [33] Besides, substitution of H atom with the CH3 group leads to a stronger cooperative ability. In contrast, the cooperativity between the H-bonds is weaker when H atom is substituted by the halogen atoms.…”
Section: Interaction Energies and Cooperativitymentioning
confidence: 99%
“…This result is consistent with the report of complexes HX•••nH2O/S (X = F, Cl, Br). [23] The interaction energies of R-1O are more than twice as many as R-1S, and the interaction energies of R-2O are triple as large as R-2S. Adding H2Z molecule to R-1Z (R = H, F, Cl, Br, CH3, and Z = O, S) causes an increase in the number of H-bonds, leading to a larger strength of complexes.…”
Section: Interaction Energy and Cooperative Energymentioning
confidence: 99%
“…The complex (HCl) [44][45][46] Fourier transform infrared (FTIR) spectroscopy in supersonic jets, 47,48 inert matrices [49][50][51][52][53][54] and Helium nanodroplets, [55][56][57] time-of-flight mass spectrometry and velocity-map imaging used to observe vibrational predissociation of the complex 58,59 and infrared cavity ringdown spectroscopy. 60,61 Many theoretical analyses using ab initio electronic structure methods [62][63][64][65][66][67][68][69][70][71][72][73][74][75][76] were published as well.…”
Section: Introductionmentioning
confidence: 99%